Regulation of Blood Flow at the Onset of Exercise by Feed Forward and Feedback Mechanisms - Hughson, R. L. (Canadian Journal of Applied Physiology, 2003)
Blood flow adapts quickly after the onset of exercise to meet the metabolic demands of skeletal muscle. This review approaches the issue of how rapidly blood flow adapts and what the mechanisms for adaptation are primarily from a control theory perspective. Several recent papers have suggested that O2 transport proceeds at a rate that anticipates the metabolic demand over a very wide range of work rates. When considered from a control theory perspective, this implies involvement of feed forward control. Although there is one very important feed forward mechanism in the muscle pump that is activated with the onset of exercise, other evidence suggests that adjustment of blood flow to match the metabolic demand relies on feedback control from local dilator factors released in proportion to the metabolic demand. These distinct mechanisms with different onset times mean that blood flow adapts to the exercise demand with at least two distinct phases. The time course of the adaptation varies greatly between work rates, showing that blood flow control cannot be described by a linear control system and that the mechanisms responsible for vasodilation are dependent on work rate.